2011
DOI: 10.1002/pbc.23273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PET‐CT on involved field radiotherapy design for pediatric Hodgkin lymphoma

Abstract: Incorporation of PET-CT information was found to influence IFRT design in 17% of patients, with most having more extensive radiotherapy fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Similarly, although 7 patients received their auBMT in third or greater remission before 2002, only 2 did so after 2001. Improvements in disease detection and fine tuning of diagnosis and initial therapy may enable physicians to better risk stratify patients and evaluate treatment response, improving initial therapy and better indicating which patients are best suited to undergo auBMT for their rrHL [2,27,28]. An important factor in determining which patients are most suited for transplantation is disease status as detected by PET-CT. Those patients with positive PET-CT before auBMT are at much higher risk of having therapy failure [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although 7 patients received their auBMT in third or greater remission before 2002, only 2 did so after 2001. Improvements in disease detection and fine tuning of diagnosis and initial therapy may enable physicians to better risk stratify patients and evaluate treatment response, improving initial therapy and better indicating which patients are best suited to undergo auBMT for their rrHL [2,27,28]. An important factor in determining which patients are most suited for transplantation is disease status as detected by PET-CT. Those patients with positive PET-CT before auBMT are at much higher risk of having therapy failure [21].…”
Section: Discussionmentioning
confidence: 99%
“…1,9 In addition, multiple retrospective studies have shown that the incorporation of PET into treatment planning for lymphoma leads to significant alterations in treatment volume. [10][11][12] As a result, the inclusion of PET/CT in treatment planning is now standard practice; FDG-PET is mandatory for INRT and ideal for the application of ISRT. 12 As previously mentioned, there are many challenges in interpreting PET data.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent management impact was avoiding radiotherapy of soft-tissue masses in HL, which did not show significant hypermetabolism on 18 F-FDG PET scans at the end of therapy. In 17% of advanced-stage HL, additional disease sites detected on 18 F-FDG PET/CT compared with CT alone resulted in an extended radiation field (33).…”
Section: Therapy Response Assessmentmentioning
confidence: 99%
“…The sensitivities and specificities of 18 F-FDG PET/CT or 18 F-FDG PET for initial staging of malignant lymphomas are 96%-99% and 95%-100%, respectively (Table 1) (11,12,14,33,34). 18 F-FDG PET is more sensitive than CT in detecting nodal and extranodal lesions in HL and NHL, including lesions in the spleen and bone marrow ( Fig.…”
Section: Initial Stagingmentioning
confidence: 99%